Efektivitas Audit Internal Pada Perguruan Tinggi Negeri Di Provinsi Sumatera Utara - Deliana Deliana; Abdul Rahman (Kajian Akuntansi, 2020)
This study aims to determine how the effectiveness of internal audit  in State Universities in North Sumatra Province. This research was conducted by distributing questionnaires and conducting interviews with several people involved in the Satuan Pengawas Interen (SPI) consisting of the SPI chairperson, team leader and examiner. The results of this study indicate that the effectiveness of internal audit in State Universities in North Sumatra Province has been effective.Keywords: Internal Audit Effectiveness, Top Management Support, Audit Findings